Application of Couple Card Media to Increase Student Activeness in Elementary Schools - Syafira Amini; Iis Nurasiah; Arsyi Rizqia Amalia (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research is motivated by the need for more student activeness in learning at elementary schools. The research aims to enhance student activeness in using couple card media among elementary school students. The research employed Classroom Action Research (CAR) with the Kemmis and McTaggart model design. The research implementation plan includes planning, action and observation, and reflection. Data collection techniques involve observation sheets, interviews, field notes, and documentation. Data processing techniques involve calculating average values and percentages. The results obtained in the pre-cycle phase showed that out of 30 students, only 41% (12 students) were active in the learning process. After implementing the first cycle using couple card learning media, student activeness improved but still needed to be maximized, with a percentage of 67% (20 students) being active in the learning process. Following the implementation of the second cycle, student activeness significantly increased and reached the predetermined threshold set by the researcher as an indicator of activeness in learning. The percentage obtained was 89% (27 students) actively engaged during the learning process.